A novel heme-thiolate peroxygenase AaeAPO and its implications for C-H activation chemistry - Wang, Xiaoshi (Springer Theses. Recognizing Outstanding Ph.D. Research, 2016)
AaeAPO, a novel extracellular heme-thiolate peroxygenase, from the agaric fungus Agrocybe aegerita was recently discovered to catalyze the cytochrome P450-like monooxygenation of diverse organic compounds, using hydrogen peroxide as a cosubstrate. In this dissertation, the function and mechanism of alkane hydroxylation reactions catalyzed by AaeAPO are addressed. In Chap. 1, current studies on the functions and mechanisms of heme-thiolate enzymes are reviewed. In Chap. 2, AaeAPO is found to catalyze various alkane hydroxylation reactions with high efficiency and selectivity. In Chap. 3, the hydroxylation event is probed with intramolecular kinetic hydrogen isotope effect substrates and radical clocks. Reasonable KIEs and the presence of radical rearranged alcohol products indicate the hydrogen atom abstraction step and the rebound mechanism. In Chap. 4, AaeAPO compound I (oxo-FeIV porphyrin radical cation) is detected and kinetically characterized by using the UV-vis, rapid-mixing stopped-flow spectroscopy. The kinetics of AaeAPO-I toward a panel of alkanes is directly measured and results in extraordinarily fast second-order rate constants. Both the shape and slope of Brønsted-Evans-Polanyi plot suggest that the reaction is entropically controlled with an early transition state for weaker C-H bonds. Additionally, in Chap. 5, the redox potentials of the couple AaeAPO-I/ferric AaeAPO are determined over a wide range of pHs, based on the reversible oxygen atom transfer between AaeAPO-I and halide ions. This analysis has allowed the highly reactive AaeAPO-I intermediate to be placed on an absolute energy scale for the first time. In Chap. 6, the rebound intermediate, AaeAPO compound II (FeIV-OH), is generated with a high yield by a one-electron direct reduction of AaeAPO-I, using nitroxides as the reducing reagents. AaeAPO-II is characterized to have a basic pKa of 10. The protonated nature of...